Determination of effective energy capacity of the conveyor when transporting different waste of mechanical treatment - Chasov, Dmytro; Belmas, Ivan; Vernyhora, Viktor; Kolyada, Bogdan (Technology audit and production reserves, 2020)
The object of research is the process of transportation of mechanical waste from the machine tool to the area of further processing using a modernized screw conveyor. One of the biggest problems in the transportation of mechanical waste remains the high cost of auxiliary processes, which form the final cost of the product. Since it is impossible to reduce the cost by excluding the stages of transportation and processing from the technological process, the energy component of the issue remains. Reducing energy costs at all stages of machining, transportation and processing is an important economic and environmental challenge. In this work, the energy consumption of the conveyor is determined during the transportation of the shavings obtained during the end turning of the gear rim of the wheel. Also, the work is devoted to the movement of sludge obtained by surface grinding of the cover of a cylindrical gearbox. The examined shavings and sludge are in different states: dry, wet and unprepared. The analysis of the existing effective equipment for cleaning and moving with the stages of cleaning and processing of cutting fluids, shavings and sludge, taking into account the energy intensity, is carried out. A comparative analysis of the energy consumption of the conveyor, taking into account the energy consumption for the preparation of the transported material – the drying process, is carried out. Recommendations are given regarding the cases of using a dryer for the preparation of shavings and sludge for the processes of moving to the processing, cleaning or disposal zones. The effective values of the energy consumption of the conveyor are determined on the basis of graphical dependencies, based on the conditions of a given productivity. It is shown that obtaining the effective energy consumption of the conveyor is achieved due to the combined accounting of the energy consumption of the conveyor and equipment for the preparation of chips and sludge. This saves 5–7 % in energy costs for an expected performance of 12.4 g/min. As a research result, it is concluded that the effective energy consumption of the conveyor is 70–90 W/min for a given productivity of 10–12 g/min when transporting wet sludge and shavings.